2010
DOI: 10.2500/aap.2010.31.3316
|View full text |Cite
|
Sign up to set email alerts
|

Olea sublingual allergoid immunotherapy administered with two different treatment regimens

Abstract: Sublingual immunotherapy (SLIT) with monomeric carbamylated allergoid administered in accordance with the standard regimen has proven to be effective and safe. Achieving clinical benefit, however, requires a lengthy period of time so it is not very suitable for short-lasting allergies. We thus performed this study to compare an administration protocol starting in the coseasonal period (with a 4-day build-up phase) with a precoseasonal scheme to verify if the former regimen provides the same benefit in a shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The frequency of discontinuation with coseasonal initiation was 7% or less in the remaining SLIT studies (see Table E4 in this article's Online Repository at www.jaci-inpractice.org). [17][18][19][20][26][27][28][29][30][31] This discontinuation rate is similar (ranges from 1% to 6%) to published data for treatment initiation outside of the season. 32,33 Systemic allergic reactions in SLIT coseasonal initiation studies…”
Section: Discontinuations In Slit Coseasonal Initiation Studiessupporting
confidence: 81%
See 3 more Smart Citations
“…The frequency of discontinuation with coseasonal initiation was 7% or less in the remaining SLIT studies (see Table E4 in this article's Online Repository at www.jaci-inpractice.org). [17][18][19][20][26][27][28][29][30][31] This discontinuation rate is similar (ranges from 1% to 6%) to published data for treatment initiation outside of the season. 32,33 Systemic allergic reactions in SLIT coseasonal initiation studies…”
Section: Discontinuations In Slit Coseasonal Initiation Studiessupporting
confidence: 81%
“…In the prospective, observational studies reported by Sieber et al, 16 the severe AEs were not specifically described, but 89% of all AEs (coseasonal and outof-season initiation combined) during titration were assessed as mild to moderate. In the prospective, open-label RCT reported by Leonardi et al,18 no severe AEs were reported with coseasonal initiation or preseasonal initiation. In the SLIT DBPC-RCT published by Reich et al, 30 the rate of severe AEs was 4% in subjects receiving coseasonal initiation versus 0% in subjects receiving placebo (Table E4).…”
Section: Severe Aes In Slit Coseasonal Initiation Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…They found that SLIT reduced dyspnea and conjunctivitis scores and cutaneous allergen reactivity compared with placebo 15. However, few subsequent studies have evaluated SLIT in olive-associated AR, and when so, such studies have been small, and/or of short duration 16. Patients with olive sensitivity usually form a minority of a larger study cohort 5,17…”
Section: Introductionmentioning
confidence: 99%